A common protocol for reliable comparison of pollen fatty acid profiles: highlighting pitfalls and proposing a methodology for ecological research - Villagómez, Gemma Nydia; Brachvogel, René-Chris; Kárpáti, Zsolt; Leonhardt, Sara D.; Schmitt, Thomas; Ruedenauer, Fabian A. (Frontiers in Ecology and Evolution, 2023)
Introduction Pollen is an important tissue in plants that plays a vital role in plant reproduction as it carries male gametes and occasionally also serves as a pollinator reward. There has been an increasing interest in pollen chemistry due to the impact of chemical variation on pollinator choices and well-being, especially in bees. The pollen fat content and lipid-to-protein ratio have been shown to play a crucial role in regulating pollen intake, and some bee species avoid overconsumption of fatty acids while specific pollen fatty acid ratios are essential for bee cognition. Therefore, knowledge of the fatty acid composition of plant pollen is crucial for understanding plant-pollinator interactions. However, existing methods for fatty acid analyses are not always specific to pollen fatty acids, and non-pollen-derived fatty acids can easily contaminate samples, making comparison between different methods impossible. Hence, the objectives of our study were to highlight the common mistakes and pitfalls made during pollen fatty acid extraction and analysis and propose a common protocol for reliable comparisons of pollen samples. Methods The proposed method, developed in two different labs using different gas chromatograph/mass spectrometers and gas chromatograph/flame ionization detectors, involved manually homogenizing pollen, extracting it with chloroform:methanol (2:1), and analyzing it using gas chromatography (GC) and mass spectrometry (MS) and a flame ionization detector (FID) for identification and quantification. Results We found that many fatty acids were present in plastic materials and many solvents commonly used in the labs, cautioning against the use of plastic and recommending blank samples to determine the level of contamination. We also suggest adding an internal standard and checking the MS and FID’s saturation limit before starting pollen homogenization. Discussion Our proposed method generated reliable fatty acid profiles of pollen from two different plant species analyzed in the two labs, and we hope it serves as a blueprint for achieving a common methodology for characterizing and comparing pollen fatty acid profiles in ecological research.